Reforming of ethanol in hybrid plasma catalytic system - Nedybaliuk, O.A.; Chernyak, V.Ya.; Fedirchyk, I.I.; Demchina, V.P.; Nedybaliuk, A.F. (Вопросы атомной науки и техники, 2018)
Influence of reaction chamber material on the hybrid plasma-catalytic reforming of model hydrocarbon was studied using same size quartz and steel reaction chambers. NO bands were shown to disappear from the plasma emission spectra during the ethanol reforming. Reforming in steel reaction chamber showed higher reforming efficiency and hydrogen energy yield than the reforming in a quartz reaction chamber. Вплив матеріалу реакційної камери на гібридне плазмово-каталітичне реформування модельного вуглеводню було досліджено за допомогою кварцової та стальної реакційних камер однакового розміру. Показано, що смуги NO зникають з емісійного спектра плазми під час реформування етанолу. Реформування етанолу в сталевій реакційній камері показало вищі ефективність реформування та енергетичний вихід водню, ніж у кварцовій реакційній камері. Влияние материала реакционной камеры на гибридное плазменно-каталитическое реформирование модельного углеводорода было исследовано с помощью кварцевой и стальной реакционных камер одинакового размера. Показано, что полосы NO исчезают с эмиссионного спектра плазмы во время реформирования этанола. Реформирование этанола в стальной реакционной камере показало более высокие эффективность реформирования и энергетический выход водорода, чем в кварцевой реакционной камере.